Analisis Kelayakan Usaha Home Industri Cookies dari Pohon Pisang di Kelurahan Pulutan Kota Salatiga - Elan Nopriadi; Siti Nur Hamidah Aliyanti; Heru Prastyo (Jurnal Syntax Transformation, 2022)
Banana is a horticultural plant that is spread throughout Indonesia. Banana production in Indonesia is high with a value of 7,264,379 tons/year. Banana production has a fairly high by-product, one of the by-products is banana trees. Banana trees can actually be used as processed food and this has been applied by the home industry in the Pulutan Village, Salatiga City. This study aims to determine the feasibility of a banana tree cookie home industry in Pulutan Village, Salatiga City. The research method uses quantitative descriptive analysis techniques in the form of SWOT Analysis, BEP, and R/C Ratio. The results of the analysis of the R/C Ratio > 1, it means that the business is feasible to develop